The Metis Effect: The Subjective Career Crafting of Working Mothers - Crowley-Henry, Marian (Socialinė teorija, empirija, politika ir praktika, 2025)
By using the metaphor of Metis, this paper explores – through a feminist standpoint theory lens – how women’s work identity may be overshadowed by their motherhood identity in the ubiquitous patriarchal neoliberal context, and how women seek to overcome the constraints imposed on them in their paradoxical roles as mother-workers by career crafting. Drawing on the whole-life conceptualization of careers where a career includes the work and nonwork domains within which jobs and paid work experiences unfold, this paper explores the subjective career crafting of mothers (supported via the Metis metaphor) in their lived performance of the societally conflicting roles of a good employee and a good mother, moving within and between work and nonwork social spaces. Career crafting considers the cognitive, task, and relational activities that can be agentially tailored to best fit one’s career within the demands of one’s different roles. Mothers’ complex, paradoxical, and boundary-crossing positions in the work–nonwork domain are considered in light of career crafting literature and the Metis metaphor.